Overexpression of proinflammatory cytokines in dental pulp tissue and distinct bacterial microbiota in carious teeth of Mexican Individuals - Gómez-García, Ana Pamela; López-Vidal, Yolanda; Pinto-Cardoso, Sandra; Aguirre-García, María Magdalena (Frontiers in Cellular and Infection Microbiology, 2022)
The prevalence of dental caries in the Mexican adult population aged 20 to 85 years is around 93.3%, and 50% in Mexican children and adolescents. Worldwide, it is the most common non-communicable disease. One of the main etiological factors for dental caries is the oral microbiome and changes in its structure and function, with an expansion of pathogenic bacteria like Streptococcus mutans. The exposed dental pulp tissue triggers an innate immune response to counteract this bacterial invasion. The relation between oral dysbiosis and innate immune responses remains unclear. We aimed to understand the relationship between innate immune response and the oral microbiota by quantifying the expression of Toll-like receptors (TLRs) and proinflammatory markers (cytokines and a chemokine) in dental pulp tissue, either exposed or not to carious dentin, and to correlate this information with the oral microbiome found in healthy teeth and those with moderate caries. RNA was purified from pulp tissue, subjected to RT-qPCR and analysed with the ΔΔCt method. Supragingival dental plaque of non-carious teeth and dentin of carious teeth were subjected to 16S targeted sequencing. Principal coordinate analysis, permutational multivariate ANOVA, and linear discriminant analysis were used to assess differences between non-carious and carious teeth. Correlations were assessed with Spearman´s test and corrected for multiple comparisons using the FDR method. The relative abundance (RA) of Lactobacillus, Actinomyces, Prevotella, and Mitsuokella was increased in carious teeth; while the RA of Haemophilus and Porphyromonas decreased. Olsenella and Parascardovia were only detected in carious teeth. Significant overexpression of interleukin 1 beta (IL1 β), IL6, and CXCL8 was detected in pulp tissue exposed to carious dentin. IL1β correlated positively with TLR2 and Actinomyces; yet negatively with Porphyromonas. These findings suggest that immune response of pulp tissue chronically exposed to cariogenic microbiome is triggered by proinflammatory cytokines IL1β and IL6 and the chemokine CXCL8.